2018
DOI: 10.1152/japplphysiol.00898.2016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic imaging in exercise physiology

Abstract: This minireview focuses on selected, noninvasive imaging techniques that have been used in the study of exercise physiology. These imaging modalities can be roughly divided into two categories: tracer based and nontracer based. Tracer-based methods use radiolabeled substrates whose location and quantity can subsequently be imaged once they are incorporated into metabolic processes. Nontracer-based imaging modalities rely on specific properties of substrates to identify metabolites and determine their concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…However, due to the limitations of EMG ( Farina et al, 2004 ) the detection of asymmetric muscle activity, especially in mildly disabled PwMS, is challenging. As suggested by Rudroff et al (2015 , 2017 ) positron emission tomography (PET) with [ 18 F]-fluoro-deoxy-glucose ([ 18 F]-FDG) as a glucose analog can be used to monitor cumulative muscle activity during exercise. In an FDG-PET study Rudroff et al (2014) found that mildly disabled PwMS had greater FDG uptake in the knee and hip flexor muscles than healthy controls after 15 min treadmill walking at a self-selected speed.…”
Section: Muscle Function Asymmetriesmentioning
confidence: 99%
“…However, due to the limitations of EMG ( Farina et al, 2004 ) the detection of asymmetric muscle activity, especially in mildly disabled PwMS, is challenging. As suggested by Rudroff et al (2015 , 2017 ) positron emission tomography (PET) with [ 18 F]-fluoro-deoxy-glucose ([ 18 F]-FDG) as a glucose analog can be used to monitor cumulative muscle activity during exercise. In an FDG-PET study Rudroff et al (2014) found that mildly disabled PwMS had greater FDG uptake in the knee and hip flexor muscles than healthy controls after 15 min treadmill walking at a self-selected speed.…”
Section: Muscle Function Asymmetriesmentioning
confidence: 99%
“…Based on the crucial role of oxygen availability for cognition together with findings suggesting that physical activity positively influences oxygen availability and cognitive performance, neuroimaging tools that can quantify tissue oxygenation (metabolism) and hemodynamics (blood flow) seem especially suitable to answer emerging research questions in the field of exercise–cognition science (for review of emerging research questions please see References [17,18,19,20]). While cerebral oxygenation and hemodynamics can be quantified with functional magnetic resonance imaging (fMRI), positron-emission-tomography (PET) and functional near-infrared spectroscopy (fNIRS) [21,22,23,24], electroencephalography (EEG) is a frequently used electrophysiological technique to record the electric signals of the brain [25,26,27,28]. However, all mentioned neuroimaging techniques have unique methodological advantages and disadvantages that have to be traded off with regard to the intended research purpose.…”
Section: Introductionmentioning
confidence: 99%
“…However, fMRI acquisition costs are relatively high, fMRI is susceptible to movement artefacts (e.g., requires rigorous head stabilization), fMRI is relatively noisy during the measurements, fMRI provides a relative low temporal resolution (e.g., ≈0.5 Hz), and fMRI cannot be used in special cohorts (e.g., individuals with metallic implants or claustrophobia) [29,30,32,34,35,36]. PET allows the assessment of changes in various substances (e.g., glucose), but PET scans are relatively expensive and repeated measurements within short time intervals are ethically not feasible due to the use of radioactive tracer substances [22,31]. EEG, which measures the brain activation directly and non-invasively based on neuroelectric signals of neurons [37], offers a high temporal resolution (e.g., >1000 Hz) but suffers from a relatively weak spatial resolution (e.g., ≈5.0–9.0 cm) [27,29,30,38,39,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, FDG-PET under resting conditions has a strong promise for unraveling the influence of multiple tDCS sessions on neuronal integrity and for revealing potentially neuroprotective and restorative tDCS mechanisms in vivo, which is of particular interest in aging and neurological disease research. A major advantage of FDG-PET over other neuroimaging techniques, like fMRI, is that whole-body scans of a single subject cannot only provide information about the brain (Table 1), but also spinal cord activity [33], and skeletal muscle energy use [34,35]. Accordingly, future studies should investigate the interactions between energy use in the CNS and skeletal muscles after tDCS (e.g., in motor performance interventions).…”
Section: How Tdcs Studies Can Benefit From Fdg-petmentioning
confidence: 99%